Reframing labour market mobility in global finance: Chinese elites in London's financial district. Issue 5 (28th May 2019) - Hall, Sarah
ABSTRACT: In this paper, I use the case of elite Chinese financial mobility to London's financial district to argue that comparatively neglected forms of elite financial migration from beyond the Global North provide important insights into the changing geographical form, and labour market practices within, leading international financial centres. Empirically, the paper identifies a distinctive geographical footprint of Chinese financial mobility to London in terms of both financial services activity and residential choices. Theoretically, I argue that explaining this geography requires work on highly skilled migration that typically privileges the economic motivations underpinning mobility to engage more fully with wider debates in economic geography that examine the inter-dependencies and inter-relationships between states and markets. These findings raise important questions surrounding the durability of Chinese finance in London, its relationship to global finance in London more generally, and wider understandings of elite financial labour markets.